The GCC in Crisis: Explorations of 'Normlessness' in Gulf Regionalism. Issue 2 (2nd April 2020) - Sadiki, Larbi; Saleh, Layla
ABSTRACT: In a field that is so loosely theorised, an investigation into intra-GCC conflict is both apposite and challenging. Empirically, interventions by Gulf states have proliferated across the GCC and MENA since 2011. This Special Issue seeks to fill a void in scholarship by looking at the ongoing crisis through the lens of norms. A hypothesised 'normlessness' has taken root: a collapse of (local) guiding principles, some even laid down by member states. Disregard for norms of non-intervention, popular sovereignty, mediation, alliance-making and social solidarity poses risks for (sub)regional stability. Provisionally, one notable weakness lies in prescriptive and proscriptive (regulative) norms pertaining to intra-GCC rules of engagement.